Age and Dyssynergia Subtypes Associated With Normal Sphincter Pressures in Women With Fecal Incontinence. Issue 3 (May 2018) - James-Stevenson, Toyia; Xu, Huiping; Heit, Michael; Shin, Andrea
Abstract : Objectives: Fecal incontinence (FI) is frequently associated with low sphincter pressures, sensory abnormalities, and advanced age. Twenty-three percent of patients with FI and 22% of healthy patients demonstrate dyssynergic defecation (DD) on high-resolution anorectal manometry. Overflow incontinence occurs in some DD patients with normal resting and squeeze anal sphincter pressures. Our aim was to identify factors associated with normal sphincter pressures in women with FI. Methods: We reviewed medical records of 134 women with FI. Patients with normal resting and squeeze anal pressures were compared with those with abnormal pressures using Wilcoxon rank sum test and Fisher exact. Multivariable logistic regression was performed to identify factors associated with normal resting and squeeze anal pressures. Results: Among 134 women, abnormal resting and/or squeeze pressures were identified in 113 and normal pressures were identified in 21. Women with normal sphincter pressures were younger (mean age 52.7 ± 10.8 years vs 59.0 ± 14.0 years, P = 0.036), more often had abnormal defecation indices (100% vs 83.2%, P = 0.043) and higher rectal defecation pressures (30.8 ± 18.8 mm Hg vs 50.8 ± 22.6 mm Hg, P < 0.001). There was an overall association between DD subtype and normal and abnormal sphincter pressure groups ( P = 0.021). Dyssynergia subtypes I or III (odds ratio, 7.2; 95% confidence interval, 1.8–28.8) and age younger than 67 years (odds ratio, 8.5; 95% confidence interval, 1.5–48.6) were associated with greater odds of having normal sphincter pressures. Conclusions: Female FI patients with normal anal sphincter pressures are younger, have higher rectal defecation pressures, and more often have type I or type III DD.